2013
DOI: 10.1111/1574-6968.12204
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria: prevalence rates of causal microorganisms, etiology of infection in different patient populations, and recent advances in molecular detection

Abstract: Bacteriuria, or the presence of bacteria in urine, is associated with both asymptomatic and symptomatic urinary tract infection and underpins much of the dynamic of microbial colonization of the urinary tract. The prevalence of bacteriuria in dissimilar patient groups such as healthy adults, institutionalized elderly, pregnant women, and immune-compromised patients varies widely. In addition, assessing the importance of 'significant bacteriuria' in infected individuals represents a diagnostic challenge, partly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
73
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 92 publications
4
73
2
5
Order By: Relevance
“…37 This in turn is a consequence of microbial colonization of the urinary tract. The occurrence of the infection among the hospitalized patients belonging to different groups varies considerably Ipe et al 20 The patients can be grouped as healthy adults, elderly patients, pregnant women and immune compromised and the extent of prevalence of UTI among these groups significantly varies.…”
Section: Urinary Tract Infection: An Overview Of the Infection And Thmentioning
confidence: 99%
See 2 more Smart Citations
“…37 This in turn is a consequence of microbial colonization of the urinary tract. The occurrence of the infection among the hospitalized patients belonging to different groups varies considerably Ipe et al 20 The patients can be grouped as healthy adults, elderly patients, pregnant women and immune compromised and the extent of prevalence of UTI among these groups significantly varies.…”
Section: Urinary Tract Infection: An Overview Of the Infection And Thmentioning
confidence: 99%
“…37 This in turn is a consequence of microbial colonization of the urinary tract. The occurrence of the infection among the hospitalized patients belonging to different groups varies considerably Ipe et al 20 The patients can be grouped as healthy adults, elderly patients, pregnant women and immune compromised and the extent of prevalence of UTI among these groups significantly varies.38 Evaluation of bacteriuria among infected individuals symbolizes a diagnostic challenge due to the involvement of variety of microorganisms and requires a careful assessment to evaluate the etiologies as a consequence of bacteriuria among the different groups of patients. Treatment during pregnancy is very crucial and the employment of empirical treatment or misuse of the antimicrobial agents due to lack of proper assessment of the condition has resulted in a widespread resistance among the pathogens conferring UTI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Pyelonephritis has been associated with maternal septicemia, renal dysfunction and anemia, 8 as well as adverse fetal outcomes, such as low birth weight and preterm birth. 3,9 Conversely, a recent study found asymptomatic bacteriuria was not associated with preterm birth. 4 Hence, the relationship between asymptomatic bacteriuria and pregnancy complications is uncertain.…”
mentioning
confidence: 94%
“…Escherichia coli is the most prevalent species isolated from humans with subclinical bacteriuria but Proteus mirabilis, Klebsiella pneumoniae, Enterobacter spp., Pseudomonas aeruginosa, Enterococcus spp., and Staphylococcus aureus also have been implicated (Ipe et al, 2013). Subclinical bacteriura in healthy female dogs has recently be reported in association with E.…”
Section: Discussionmentioning
confidence: 98%